Yemen : Workforce Development - World Bank (Washington, DC, 2015)
Yemen, which belongs to the category of Least Developed Countries according to the OECD s Development Assistance Committee, has faced many challenges during the last two decades in its endeavor to achieve an acceptable level of economic development. To inform policy dialogue on these important issues, this report presents a comprehensive diagnostic of the country s WfD policies and institutions. The results are based on a new World Bank tool designed for this purpose. Known as SABER-WfD, the tool is part of the World Bank s initiative on Systems Approach for Better Education Results (SABER), whose aim is to provide systematic documentation and assessment of the policy and institutional factors that influence the performance of education and training systems. The SABER-WfD tool encompasses initial, continuing, and targeted vocational education and training that are offered through multiple channels, and focuses largely on programs at the secondary and post-secondary levels. The tool is based on an analytical framework3 that identifies three functional dimensions of WfD policies and institutions: (1) Strategic framework, which refers to the praxis of advocacy, partnership, and coordination in relation to the objective of aligning WfD in critical areas to priorities for national development; (2) System Oversight, which refers to the arrangements governing funding, quality assurance, and learning pathways that shape the incentives and information signals affecting the choices of individuals, employers, training providers and other stakeholders; and (3) Service Delivery, which refers to the diversity, organization, and management of training provision, both state and non-state, that deliver results on the ground by enabling individuals to acquire market- and job-relevant skills.